1998
DOI: 10.1016/s0006-3495(98)77567-8
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Characterization of the High-Affinity Cation-Binding Site of the Purple Membrane

Abstract: Binding of Mn2+ or Mg2+ to the high-affinity site of the purple membrane from Halobacterium salinarium has been studied by superconducting quantum interference device magnetometry or by ab initio quantum mechanical calculations, respectively. The binding of Mn2+ cation, in a low-spin state, to the high-affinity site occurs through a major octahedral local symmetry character with a minor rhombic distortion and a coordination number of six. A molecular model of this binding site in the Schiff base vicinity is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…(b) Identification of the color determining metal binding site. It has been suggested that the high affinity metal site which determines the state of protonation of Asp‐85 is located in the retinal binding pocket, directly interacting with one or more of the charged residues: Asp‐85, Asp‐212 and SBH + [12, 23, 26–28]. Such a location has been seriously questioned by a recent study of the kinetics of the blue⇔purple transition, as induced by large molecular cations [29].…”
Section: Introductionmentioning
confidence: 99%
“…(b) Identification of the color determining metal binding site. It has been suggested that the high affinity metal site which determines the state of protonation of Asp‐85 is located in the retinal binding pocket, directly interacting with one or more of the charged residues: Asp‐85, Asp‐212 and SBH + [12, 23, 26–28]. Such a location has been seriously questioned by a recent study of the kinetics of the blue⇔purple transition, as induced by large molecular cations [29].…”
Section: Introductionmentioning
confidence: 99%
“…This is a clear indication that Glu 194 forms part of XЈH, the group coupled to the Asp 85 pK a . From the time when the presence of divalent cations in the purple membrane was described, numerous efforts have been devoted to identify their role and location (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Some authors claim a nonspecific location of the cations in the double layer (18,21,22) or in the lipid phase (26).…”
mentioning
confidence: 99%
“…Some authors claim a nonspecific location of the cations in the double layer (18,21,22) or in the lipid phase (26). However, the majority of works argue for the existence of specific binding sites in the purple membrane, including a site near Asp 85 (24,27,28), or a more external location (29,30). Among the most outstanding results pointing toward specific cation locations in the protein moiety are: (i) the evidence for carboxyl participation in cation binding from studies using specific reagents (13,17); (ii) the presence of fewer cation-binding sites and with lower affinity in the bleached and pink membranes as compared with purple membranes (14,16,19), even that the electric surface potential of bleached membrane remains unchanged (31); (iii) extended x-ray absorption fine structure data describing a different environment for the bound Mn 2ϩ with respect to free Mn 2ϩ in water and ruling out the interaction of Mn 2ϩ with P or S atoms (32); (iv) Fourier transform infrared studies showing that binding of Mn 2ϩ to deionized membrane induces changes in the reverse turns, located in the loops (33); and (v) 13 C NMR studies detecting changes in the Ala 196 environment upon divalent cation binding (25).…”
mentioning
confidence: 99%
“…Thus, Tuzi et al using 13 C NMR techniques proposed the existence of a cation binding site located on the loop between helices F and G,14 Eliash et al have shown a Mn 2+ ‐specific binding site on the extracellular part of the membrane,15 and Sanz et al established Glu194 and Glu204 as residues involved in cation binding 16. In addition, a high‐affinity binding site located near the retinal pocket had also been suggested by several authors 17–24…”
Section: Introductionmentioning
confidence: 93%
“…Assuming similar binding behavior to Ca 2+ due to its high relative mass and electronic properties, Mn 2+ is a useful experimental probe to analyze the structural role of bound cations as well as their localization in BR. In particular, Mn 2+ regenerated BR has been studied using electron spin resonance (ESR),7 Fourier transform infrared spectroscopy (FTIR),25 magnetic susceptibility,20 and extended x‐ray absorption fine structure (EXAFS) measurements21, 26 to analyze the structural role, as well as the possible localization of the bound cations. The binding of the Mn 2+ cations to the deionized membrane consist of a high‐affinity site, three sites of medium, and one site of low affinity 7…”
Section: Introductionmentioning
confidence: 99%